Voices of Rondo : oral histories of Saint Paul's historic Black community - Cavett, Kate; Cavett, Kate; Taylor, David Vassar, 1945- (Fesler-Lampert Minnesota heritage book series., 2017)
"Stories told through the eyes of Saint Paul's historic Rondo community illuminate the northern urban Black experience during the first half of the twentieth century. We glimpse the challenges of racism and poverty and share the victories of a community that educated its children to be strong, find personal pride, and become the next generation of leaders in Minnesota and beyond"--